Performance of Computed Tomography of the Kidneys, Ureter and Bladder in Non-Calculus Diagnoses: A Comparative Review of Non-Enhanced with Intravenous Contrast-Enhanced Imaging - Alexander T. O’Mahony; Michael G. Waldron; David J. Ryan; Brian Carey; Sahil Shet; Eid Kakish; Patrick O'Regan; David Glynn; Josephine Barry; Owen J. O'Connor; Michael M. Maher (Diagnostics)
Background/Objectives: Non-enhanced computed tomography of the kidneys, ureters and bladder (NECT KUB) is the initial imaging modality for suspected nephroureterolithiasis. However, for alternative diagnoses, NECT may not be the ideal technique. Our institution changed the protocol for this cohort from NECT to intravenous contrast-enhanced CT (CECT) KUB. We aimed to retrospectively compare the rate of alternative diagnosis seen and the rates of calculus detection in CECT versus NECT KUB as a means of assessing performance. Our secondary aim was to compare the radiation dose between CECT and NECT KUB. Methods: Patients referred from the emergency department with suspected nephroureterolithiasis who underwent NECT and CECT KUB over two years were included. Key performance metrics included calculus detection rate, alternative findings, and negative studies. The metrics were compared between genders and age groups. Categorical variables were analysed using Chi-squared or Fisher’s Exact Test and continuous with T-testing. Results: A total of 423 patients had CT KUB imaging (209 NECT, 214 CECT). The incidence of alternative findings in the NECT group was 23% and 40% in CECT (p < 0.001). There were 48 findings (13 major, 11 moderate and 24 minor) in NECT studies and 85 findings (23 major, 43 moderate and 19 minor) in CECT (p < 0.001). Major diagnoses ranged from acute emergencies to more indolent findings, including suspicious nodules/masses. The calculus detection rate (NECT 56%, CECT 54%, p = 0.643) and negative studies (NECT 28%, CECT 22%, p = 0.168) did not significantly differ between protocols. CECT had a mean effective dose of 8.71 ± 2.58 mSv representing 2.4 times the exposure of NECT (p < 0.001). Conclusions: CECT is associated with a greater alternative diagnosis rate with similar calculus detection rates compared to NECT KUB, suggesting superior performance. However, CECT exposes patients to significantly greater levels of ionizing radiation.